2009
DOI: 10.1371/journal.pgen.1000701
|View full text |Cite
|
Sign up to set email alerts
|

1+1 = 3: A Fusion of 2 Enzymes in the Methionine Salvage Pathway of Tetrahymena thermophila Creates a Trifunctional Enzyme That Catalyzes 3 Steps in the Pathway

Abstract: The methionine salvage pathway is responsible for regenerating methionine from its derivative, methylthioadenosine. The complete set of enzymes of the methionine pathway has been previously described in bacteria. Despite its importance, the pathway has only been fully described in one eukaryotic organism, yeast. Here we use a computational approach to identify the enzymes of the methionine salvage pathway in another eukaryote, Tetrahymena thermophila. In this organism, the pathway has two fused genes, MTNAK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…While MtnBD shows no similarity to MtnW (DK-MTP-1-P enolase), MtnX (HK-MTPenyl-1-P phosphatase), or MtnC (DK-MTP-1-P enolase/phosphatase), previous genetic experiments suggested that it catalyzes four sequential reactions; dehydration, enolization, dephosphorylation, and dioxygenation [14]. To analyze whether MtnBD catalyzes these four reactions (steps 4 to 7) in vitro , we designed a recombinant protein of T. thermophila MtnBD fused with a histidine-tag at the N-terminus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While MtnBD shows no similarity to MtnW (DK-MTP-1-P enolase), MtnX (HK-MTPenyl-1-P phosphatase), or MtnC (DK-MTP-1-P enolase/phosphatase), previous genetic experiments suggested that it catalyzes four sequential reactions; dehydration, enolization, dephosphorylation, and dioxygenation [14]. To analyze whether MtnBD catalyzes these four reactions (steps 4 to 7) in vitro , we designed a recombinant protein of T. thermophila MtnBD fused with a histidine-tag at the N-terminus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gene fusions of mtnA and mtnK , and mtnB and mtnD , which encode enzymes in the methionine salvage pathway (MSP), are present in the genome of T. thermophila [14]. MSP is a universal pathway in all kingdoms [15]; it recycles reduced sulfur from 5-methylthioadenosine (MTA), a by-product of polyamine synthesis, to methionine (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations